Decades of science fiction - Minyard, Applewhite 1946-. (Lincolnwood, Ill. NTC Pub. Group, 1998)
An anthology of science fiction short stories, grouped by decade from the late 1800s to the present. Includes chapter openers providing historical and social context, headnotes about the authors, and writing and discussion questions.
Keywords: Science fiction, American -- Outlines, syllabi, etc; Science fiction, English -- Outlines, syllabi, etc; Science fiction, American; Science fiction, English; Science fiction; Short stories